ARTISTIC COMPREHENSION OF THE EVENTS OF THE PERIOD IN THE NOVELS OF UTKIR KHASHIMOV - Tolganoy Mamatkulova Azamjon kizi (Journals Park Publishing, 2023)
In the article, the analysis of the wartime tragedies by Utkir Khashimov in his novels and the psyche of the characters analyzed in them, the analysis of the social problems of that time, is clearly reflected in the novels “Between Two Doors”, “Lives Lived in a Dream”, “Light is not without a shadow”.
Keywords: war, era, novel, analysis, society, psyche, problem.